Situational analysis of ‘Virtual evaluation,’ amidst the COVID-19 pandemic for future exploration! - An experience from a single-center study - Gupta, Anmol; Bhardwaj, Ashok; Gupta, Madhu; Parashar, Anupam; Sharma, Gopal Ashish (Indian Journal of Community Health, 2021)
It was 30th January 2020 when India reported its first COVID 19 in Kerala. Soon, the pandemic of SARS-CoV-2 was inevitably knocking at the doors of the small hilly state of Himachal Pradesh (HP). On 20th March 2020, HP reported its first two cases of SARS-CoV-2 in Kangra district. Since then, although the COVID-19 pandemic was ensuing in the state, the epidemic was well contained due to the extensive collective efforts of the health department and other stakeholders. COVID 19 pandemic has emerged as a significant barrier, hampering all the regular activities and impacting all spheres of life. Particularly in HP, health care services were predominantly delivered through government services across the state. As program managers, post-graduates of Community Medicine are the critical stakeholders of health care delivery at the peripheral level and integral implementers of Flu-Clinic, Contact Tracing, Surveillance and field survey teams. Ensuing pandemic enforces the need for the early placement of trained workforce in the periphery for apt delivery of specialized services amongst the community.